Clinical phenotype and long-term outcome of patients with Anderson-Fabry disease followed at a multidisciplinary cardiomyopathy centre. (3rd October 2022) - Verrillo, F; Fumagalli, C; Tassetti, L; Zocchi, C; Tanini, I; Zampieri, M; Maurizi, N; Tomberli, A; Baldini, K; Argiro', A; Cappelli, F; Girolami, F; et al.
Abstract: Background: Anderson-Fabry disease (AFD) is a rare genetic lysosomal storage disorder which often goes unnoticed until symptom onset requires aggressive treatment. Prompt diagnosis remains crucial. Dedicated multidisciplinary centres are a remarkable opportunity to develop early detection strategies and appropriate management. Purpose: To describe the long-term outcomes of patients diagnosed with AFD followed at a Cardiomyopathy Referral Centre according to baseline phenotype (clinical involvement vs sub-clinical involvement). Methods: All consecutive patients with AFD visited at our Cardiomyopathy Unit from 1989 to 2020 with >1-year follow-up were retrospectively reviewed. Clinical involvement was defined by one among left ventricular hypertrophy (LVH)>15mm, presence of conduction blocks or cardiac implantable electronic devices (CIED), atrial fibrillation, kidney disease (CKD), stroke or transient ischemic attack (TIA). The primary outcome was disease progression, defined as de novo CIED implantation, increased or de novo LVH, de novo Stroke/TIA, or progression of CKD. Of 110 patients diagnosed with AFD, 86 (78%) with >1-year follow-up were selected. Results: Clinical involvement was present in 60 (70%) patients. Age at diagnosis was similar between patients with clinical and subclinical phenotype (42+17 vs 39+15, p=0.277). Patients with clinical involvement were more frequently men (N=25 [42%] vs 4 [15%], p=0.025) and probands (p=0.01). Overall, 1-organ involvement was present in 31 (52%) patients, 2-organ involvement in 24 (40%) patients and 3-organ in 5 (8%). A total of 46 (77%) patients were referred to enzyme replacement therapy (ERT): 52% received agalsidase α, 26% agalsidase β, and 22% migalastat. Among those with a clinical involvement not on ERT, 9 (15%) were scheduled for ERT initiation, 3 (5%) were considered old for ERT, 1 (1.5%) refused ERT and 1 (1.5%) had an allergic reaction to ERT. At 7 [3–12] years follow up, both study cohorts manifested signs and symptoms of disease progression: N=28 (47%) vs N=4 (15%), p=0.01, in patients with vs. without baseline clinical involvement, respectively. The main causes for diseases progression were increase (28%) or de novo LVH (13%), CKD (7%) and CIED implantation (5%). At Cox multivariable analysis, however, after adjustment for age at diagnosis, late onset phenotype and gender, the impact of clinical vs subliclinical involvement on disease progression was lost (Hazard Ratio 0.92, 95% C.I. 0.30–2.81). Conclusion: Clinical involvement in AFD is frequent, irrespective of age at diagnosis, being present in more than 1-in-2 patients at baseline. Prompt referral to dedicated centres is warranted for appropriate care as the disease may progress in both patients with and without initial overt clinical phenotype despite optimal medical management. Funding Acknowledgement: Type of funding sources: None.